PENATALAKSANAAN TRAUMA GIGI PADA ANAK USIA TUMBUH KEMBANG - Endriyana, Jessica; Astuti, Luki; Adrian , Nova; Melaniwati; Dipankara, Jackson; Louisa, Marie (Universitas Trisakti, 2024)
Dental trauma is often found in children of growing age due to poor psychomotor coordination, making them prone to falls. This can cause damage to the teeth and their supporting tissues, which can interfere with mastication, speech, aesthetics and the eruption of permanent teeth. The management of dental trauma in children is still poorly understood by parents and teachers, therefore an approach is needed regarding the first treatment of trauma to primary teeth. The choice of Community Service target at Kepodang preschool was due to a request from the school principal as the community leader. Education and training activities were carried out on Monday, March 4th 2024 for a total of 22 teachers and parents. The aim of this activity is to increase knowledge, motivate changes in attitudes and behavior in maintaining oral health, and provide learning about first care for trauma in primary teeth. An initial assessment of knowledge and attitudes regarding first care for trauma in primary teeth was carried out through administering a pre-test with multiple choice questions. The material given includes dental and oral health problems, prevention methods, as well as first treatment for trauma in primary teeth by using the power point text, discussion, and a simulation of how to brush teeth with songs. Evaluation was carried out through a post test with multiple choice questions. Evaluation of the post test results shows that there was an increase in test score. The results of this activity recommend continuing this training activity in kindergartens or other elementary schools, especially for teachers and parents